Evaluation of Some Medicinal Herbs Cold Pressed Oils According Their Physicochemical Properties with Chemometry - Zeliha Üstün Argon; Ali Gökyer; Zinar Pınar Gümüş; Mevlüt Büyükhelvacıgil (International Journal of Secondary Metabolite)
In this study, we investigated the effects of cold pressed oil on physicochemical properties of milk thistle (Silybum marianum), anise seed (Pimpinella anisum), fennel seed (Foeniculum vulgare), terebinth (Pistacia terebinthus), coriander (Coriandrum sativum) and nettle seed (Urtica dioica). Selected oils from Central Anatolia Regions, were investigated in terms of the fatty acid methyl esters (FAME) compositions, peroxide value (PV), free fatty acid (FFA), refraction index (RI) at 40 ° C and oilseed yields. The data obtained from the analyses were evaluated chemometrically. The diagrams obtained by basic component analysis (PCA) and hierarchical clustering analysis (HCA). According to PCA and HCA results, selected seed oils have different properties in terms of FAME, FFA, PV and RI. This suggests that each oil originates from the physicochemical properties of its unique pharmacological properties. As a result, in this study, data on the physicochemical properties of oils obtained from six medicinal plants was given. These results indicate that the seeds of the Central Anatolian region can be used as acceptable raw materials for herbal natural support products. These analyses can be used in order to assure the purity and quality parameters of seed oils. And FAME, PV, FFA and RI data can be good parameters to determine any adulteration to these oils by chemometric analysis.